Associations between vaspin rs2236242 gene polymorphism, walking time and the risk of metabolic syndrome - Suliga E; Kozieł D; Cieśla E; Rębak D; Wawszczak M; Adamus-Białek W; Naszydłowska E; Piechowska A; Głuszek S (Balkan Journal of Medical Genetics, 2019)
The associations between serum vaspin levels and metabolic or coronary artery disease (CAD) and polycystic ovary syndrome (PCOS) is under the scope of current researchers. Therefore, this adipokine can be considered as a biomarker of metabolic syndrome (MetS). The aim of the study was to analyze the associations between the vaspin rs2236242 polymorphism and physical activity in relation to MetS and its components. The analysis involved the genetic material and clinical data of 108 individuals with MetS and 110 controls. Vaspin rs2236242 polymorphism was detected using the tetra-primer amplification-refractory mutation system polymerase chain reaction (T-ARMS PCR) method. The TA genotype of vaspin rs2236242 was associated with a greater risk of MetS and its components compared with the TT genotype. The analysis of interactions between genotype and walking time revealed that a walking time longer than 60 min./day significantly decreased the risk of MetS in the TA carriers (p = 0.007). The obtained results suggest that any unfavorable effect of the TA genotype of the vaspin rs2236242 polymorphism can be essentially reduced, or even reversed, in a case of individuals walking longer than 60 min. a day. The analysis of the interaction between vaspin rs2236242 polymorphism and walking showed that a walking time of longer than 1 hour a day significantly reduced the risk of MetS, elevated blood pressure and triglycerides concentration.